Impact of undissociated volatile fatty acids on acidogenesis in a two-phase anaerobic system - Maspolim, Yogananda (2016)
This study investigated the degradation and production of volatile fatty acids (VFAs) in the acidogenic phase reactor of a two-phase anaerobic system. 20 mmol/L bromoethanesulfonic acid (BESA) was used to inhibit acidogenic methanogens (which were present in the acidogenic phase reactor) from degrading VFAs. The impact of undissociated volatile fatty acids (unVFAs) on “net” VFAs production in the acidogenic phase reactor was then evaluated, with the exclusion of concurrent VFAs degradation. “Net” VFAs production from glucose degradation was partially inhibited at high unVFAs concentrations, with 59%, 37% and 60% reduction in production rates at 2190 mg chemical oxygen demand (COD)/L undissociated acetic acid (unHAc), 2130 mg COD/L undissociated propionic acid (unHPr) and 2280 mg COD/L undissociated n-butyric acid (unHBu), respectively. The profile of VFAs produced further indicated that while an unVFA can primarily affect its own formation, there were also unVFAs that affected the formation of other VFAs.